Produção de vedações elastoméricas veiculares: avaliação do nível de implementação com abordagem na economia circular - Silva, Carlos Augusto Borges da (2021)
Most of the industrially produced rubber is used in the manufacture of tires, which is around 70% of world production. Another large part of the production is used in the manufacture of automotive parts, products for medical devices, packaging, construction and other sectors. In the automotive industry, the manufacturing of parts used is in the driving system, components for sealing in the car body, control and sealing of brake fluids, refrigeration, lubrication and in the absorption from impacts and driving force. In this context, the general objective of this present work is to evaluate the production of elastomeric seals, produced from synthetic rubber and used in the automotive sector, based on the concepts of circular economy (CE) as well as through the 9R's concepts of sustainability. The method used was a bibliometric review of the scientific literature and field research in the form of a case study, carried out in three companies that produce rubber parts and seals, in which the level of implementation of the concepts of circular economy was evaluated. As results, there is a field to be explored related to the 9R’s of sustainability. It was also evaluated and observed that the recycling of rubber products, in addition to pneumatic devices, still has a very large field for the development and implementation of actions aimed at CE and 9R´s,